Modeling type Ia supernovae and quark novae - Röpke, Friedrich (Physics of particles and nuclei, 2015)
Compact astrophysical objects can change their structure and composition in combustion-like processes. In the case of white dwarfs, thermonuclear burning can even lead to an explosion as a Type la supernova. We give a brief account of the physical concepts of combustion and of methods to model this phenomenon in large-scale numerical simulations. As examples for application we discuss thermonuclear explosions of white dwarfs and to hypothetical “quark novae” transforming neutron stars into strange quark stars.
Gesehen am 02.07.2020